Sustainability of Bhutan’s Hydropower - Chhopel, Gongsar Karma (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Bhutan’s river potential for hydropower has been estimated at 30,000 MW, the majority of which is concentrated in the Wangchhu, Punatsangchhu, Mangdechhu and Drangmechhu river basins. Hydropower forms the backbone of Bhutan’s socio-economic strength: Ninety nine percentage of its electricity supply comes from hydropower generation and hydropower alone contributes of national revenue. Bhutan has been cast as a model in South Asia for its environmental conservation policy. However, the impacts of climate change are becoming evident in the form of fast-retreating glaciers and erratic precipitation patterns that will prove to be costly for the hydropower sector as the country continues to bank on this renewable natural resource. DOI: http://dx.doi.org/10.3126/hn.v14i0.11272 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 14, 2014, January Page: 73-76